Malay translation and validation of modified checklist for autism in toddlers, revised with follow-up (M-CHAT-R/F) - Ariffin, R. A.; Ismail, J.; Abd Rahman, F. N.; Wan Ismail, W. S.; Ahmad, N.; Abdul Ghafar, A.; Yang, W. W.; Masra, F.; Kamal Nor, N. (Frontiers in Pediatrics, 2024)
Introduction Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental condition diagnosed clinically based on phenotypic characteristics and criteria such as the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Due to its significant social, emotional, and psychological impacts, early identification and diagnosis are crucial for starting early intervention and improving outcomes. A screening tool is imperative in identifying young children at risk so timely intervention can be instituted. The Modified Checklist for Autism in Toddlers, Revised with Follow-up (M-CHAT-R/F) is a reliable and valid screening tool used worldwide, with the previous iteration used for a long time in Malaysia. To enhance ASD screening in Malaysia, the latest version of M-CHAT-R/F was translated into Malay and evaluated for reliability and validity, as majority of the population speaks Malay, while the tool is originally in English. This study is a cross-sectional study performed in the Universiti Kebangsaan Malaysia (UKM) hospitals, between May 1st, 2020, to June 30th, 2022. Methodology The English version of the M-CHAT-R/F was translated into Malay using forward and backward translation methods. Content and face validity were ascertained and a pilot study was performed for internal reliability. A total of 244 children attending clinics and wards in UKM hospitals aged 16-30 months were recruited based on three categories: children with typical development, suspected cases, and established cases of ASD. All caregivers of the recruited children were asked to complete the Malay M-CHAT-R/F. Reliability and validation assessments were performed. Results Malay M-CHAT-R/F was found to be a reliable tool with good internal consistency (Cronbach's alpha = 0.906, p < 0.001). The Receiver Operating Characteristic (ROC) curve showed that cut-off scores of 2 on Malay M-CHAT-R/F lead to successful ASD classification with Area Under the Curve (AUC) = 0.887, p < 0.001 with a 95% CI (0.840, 0.933). Discussion The assessment of the Malay M-CHAT-R/F showed satisfactory psychometric properties. Based on this study, the Malay M-CHAT-R/F is a reliable and valid screening tool to screen for ASD in children aged 16–30 months. Translating the M-CHAT-R/F into Malay is expected to improve community outreach and screening, which is essential for early diagnosis and timely intervention for children with ASD in Malaysia.